Effect of temperature on the photoproperties of luminescent terbium sensors for homogeneous bioassays. (16th February 2012) - Dong, Zhi‐Ning; Wu, Ying‐Song; Wang, Zheng; He, An; Li, Ming; Chen, Meijun; Du, Hongyan; Ma, Qiang; Liu, Tiancai
ABSTRACT: We developed a luminescent terbium sensor (LTS) based on energy resonance transfer for homogeneous bioassays. The effect of temperature on photoluminescence and time‐resolved fluorescence of the LTS was investigated. When the temperature was increased from 277 K to 369 K, the photoluminescence quantum yield decreased by up to 25 %, time‐resolved fluorescence decreased by up to 54 %, and the lifetime shortened dramatically. Studies showed that both photoluminescence and time‐resolved fluorescence quantum yields were largely recovered after samples were heated from 298 to 310, 333 or 369 K and subsequently cooled to 298 K. These results indicate that the homogeneous bioassay with LTS is sensitive to temperature and should be conducted at a constant temperature to ensure the temperature effect does not influence data and to increase the accuracy of the results. The results of this study are important for LTS applications in homogeneous bioassays. Copyright © 2012 John Wiley & Sons, Ltd.